2022
DOI: 10.2106/jbjs.21.01271
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Inclusion in Orthopaedic Surgery from Medical School to Practice

Abstract: :Orthopaedic surgery has historically been one of the least diverse fields in medicine in the U.S. Despite having been declared a critical issue by the American Orthopaedic Association, a lack of diversity and inclusion across all metrics remains a persistent problem. In order to balance representation within orthopaedic surgery, a multiyear and multilevel approach should be considered across the life cycle of a surgeon. Talented individuals from diverse backgrounds must be identified and given early exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Previous studies have identified a lack of minority faculty and many other potential barriers to recruiting Black and minority applicants 25 , 26 . To further improve diversity in orthopaedic surgery, efforts should focus on early exposure in medical education and improved mentorship with programs such as the Nth Dimension and the J. Robert Gladden Orthopaedic Society 23 , 25 . In addition, programs must take a proactive approach to create a safe and fair working environment for URiM residents 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified a lack of minority faculty and many other potential barriers to recruiting Black and minority applicants 25 , 26 . To further improve diversity in orthopaedic surgery, efforts should focus on early exposure in medical education and improved mentorship with programs such as the Nth Dimension and the J. Robert Gladden Orthopaedic Society 23 , 25 . In addition, programs must take a proactive approach to create a safe and fair working environment for URiM residents 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although match rates of female candidates are currently reflective of their application rates, the number of female residents pursuing orthopaedic surgery is far less than male residents. With increased early exposure in medical education with programs such as the Perry Initiative and improved female mentorship through the Ruth Jackson Orthopaedic Society and other organizations, the orthopaedic community can improve on the proportion of female candidates pursuing careers within orthopaedic surgery [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…There was noted to be a lack of gender diversity within author groups, with the 20 most published lead or senior authors being men (online supplemental table 2). A lack of gender and ethnic diversity has been highlighted by multiple sources including the American Orthopaedic Association and British Orthopaedic Association as a critical issue 105. Diversity in healthcare has been shown to be beneficial multilaterally, including in achieving improved patient communication, education and outcomes 106…”
Section: Resultsmentioning
confidence: 99%
“…As a Black medical student, I can attest to the importance of a sense of belonging in shaping my career aspirations. Despite the progress that has been made in promoting diversity and inclusion in medicine, many medical schools and training programs still lack diversity among their faculty and leadership [3]. This can create a sense of disconnection and alienation for students who do not see themselves reflected in the field.…”
mentioning
confidence: 99%
“…I have found that seeking out mentors and role models who share my background and values has been instrumental in fostering a sense of belonging and community within the field. By connecting with other Black orthopaedic surgeons and engaging with organizations that promote diversity and inclusion (such as the Student National Medical Association Orthopedic Surgery Interest Group, the J. Robert Gladden Orthopaedic Society, Nth Dimensions, the Perry Initiative, Pride Ortho, and the Ruth Jackson Orthopaedic Society) [1,3], I have been able to find a sense of purpose and motivation in my career goals. The findings of this study validate my personal experiences and underscore the need for institutional efforts to prioritize diversity, equity, and inclusion in their recruitment and retention efforts.…”
mentioning
confidence: 99%